The research and association between teaching and care in the consolidation of the Brazilian National Health System - Fortuna, Cinira Magali; Mishima, Silvana Martins; Matumoto, Silvia; Pereira, Maria José Bistafa; Ogata, Marcia Niituma (Revista da Escola de Enfermagem da USP, 2011)
This article comprises the authors' reflections about theory and experiences about the connection between research, teaching and health care services for the consolidation of the Brazilian National Health System (SUS - Sistema Único de Saúde). The research in collective health nursing face the challenge of breaking with the traditional forms that separate those who research, teach, learn and provide care. The movement for changing the process of caring and teaching occurs through an investigative and reflexive production. Therefore, the studies for the consolidation of the SUS call for an intense connection between teaching-service and knowledge production. It challenges us to create research projects together with the workers, which implies advancing the data collection to data production, and taking students to the activities and internship for the alliance and co-responsibilization of actions. We propose assuming the lack of knowledge to create instituting practices.